2012
DOI: 10.4161/trns.19734
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic in vitro transcription circuits

Abstract: With the help of only two enzymes--an RNA polymerase and a ribonuclease--reduced versions of transcriptional regulatory circuits can be implemented in vitro. These circuits enable the emulation of naturally occurring biochemical networks, the exploration of biological circuit design principles and the biochemical implementation of powerful computational models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…We formally define ''memory'' (Figure 2) in this context as a phenomenon describing the relationship between two sets of genes, namely, ''stimulus'' and ''response'' that satisfies the following conditions: (1) the stimulus activates the response and (2) the response retains its activation state even after deactivation of the stimulus (the existence of history). The fundamental signature of memory is its temporality-a longlasting and stimulus-specific change induced by a transient experience (Bacchus et al, 2013;Chechile, 2018;Durso and Nickerson, 1999;Weitz and Simmel, 2012). We consider individual nodes of a Boolean GRN as the potential targets of external stimuli and able to produce a response (output or effector nodes).…”
Section: Transcriptional Network Can Exhibit Multiple Kinds Of Memorymentioning
confidence: 99%
“…We formally define ''memory'' (Figure 2) in this context as a phenomenon describing the relationship between two sets of genes, namely, ''stimulus'' and ''response'' that satisfies the following conditions: (1) the stimulus activates the response and (2) the response retains its activation state even after deactivation of the stimulus (the existence of history). The fundamental signature of memory is its temporality-a longlasting and stimulus-specific change induced by a transient experience (Bacchus et al, 2013;Chechile, 2018;Durso and Nickerson, 1999;Weitz and Simmel, 2012). We consider individual nodes of a Boolean GRN as the potential targets of external stimuli and able to produce a response (output or effector nodes).…”
Section: Transcriptional Network Can Exhibit Multiple Kinds Of Memorymentioning
confidence: 99%
“…Surprisingly, our data indicate that naked DNA device lifetimes are greater than devices with terminal fluorophore conjugation, in contrast to studies reporting enhanced nuclease resistance with extensive Cy-dye labeling or terminal chemical modifications. 7,28,29,32,33 The potential for naked or minimally modified DNA device operation in vivo could enable regulation of enzymatic activity, 3 control of transcription, 34 and diagnostic imaging, 35 greatly expanding the biomedical applications for DNA-based devices. Applications for operation in human blood range from non-viral gene and drug delivery 17,25,[36][37][38] to disease theranostics, [39][40][41] and open the door for rationally designed protein analogs as new tools in biology, synthetic biology, and biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…The above analysis was based on basic circuits which incorporate only the protein monomer. We note that many of the template based circuits described in the literature involve only monomeric regulation. , Even in the context of transcription–translation systems, it has been shown that nonlinear behavior like bistability can be achieved through monomeric regulation alone. , The insights we have obtained continue to hold good even with protein dimerization, if the dimer is nondiffusible and does not degrade. Furthermore, if the dimer diffuses and degrades at the same rate as the monomer, the same insights hold good for the total concentration of protein (see Supporting Information, Section 7).…”
Section: Resultsmentioning
confidence: 74%